Unsur Lokalitas Dalam Tafsir Sufi Amaly - Arif Iman Mauliddin (Akademika: Jurnal Keagamaan dan Pendidikan, 2018)
This paper represent and describe the relation between sufistic interpretation (isyāri) and the ijtima’i approach in Tafsir Amaly by KH. Qayyim Ya’qub. The position of sufistic tafsir which so polemical and eccentric got challenges culturally and socially. This condition that drives KH. Qoyyim Ya’qub compile his tafsir. In addition, the approach of ijtima’i that collaborate local elements symbolically in his tafsir, intended to make the peoples understand the content of the Qur’an easily. In particular, this paper will analyze and review the dominance of locality aspects in the process of interpretation, and series of asbāb that initiate mufassir to chose that step.